Human rights and genetic engineering: legal aspects - Fiori, Angelo; Grassi, Aldo (Medicina e Morale, 2024)
The topic, in its legal aspects, draws the attention of our society - which is asking itself about the future - not only to the need to know the current state of research and applications of genetic genius, but also, indeed above all, to the opportunity to attempt some anticipations of 'tomorrow', anticipations that help to plan for the future.